2022
DOI: 10.1227/neu.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy for Cerebral Vein Thrombosis: A Propensity-Matched Analysis of Anticoagulation in the Treatment of Cerebral Venous Thrombosis

Abstract: BACKGROUND:Endovascular treatment (EVT) for cerebral vein thrombosis (CVT) has not been proven to be more effective than anticoagulation based on recent results of the Thrombolysis or Anticoagulation for Cerebral Venous Thrombosis (TO-ACT) randomized clinical trial.OBJECTIVE:To compare outcomes of EVT vs medical management in CVT.METHODS:We compared EVT vs medical management in a retrospective multinational cohort of consecutive patients with CVT across 4 countries (USA, Italy, Switzerland, and New Zealand) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Observational studies of EVTs for CVT have had mixed results, but generally show improved clinical outcomes with mechanical thrombectomy among those with severe deterioration despite systemic therapies, 41 although a recent large propensity-matched analysis from ACTION CVT showed no evidence of EVT benefit for CVT. 42 A randomized trial compared EVT to systemic anticoagulation in patients with acute CVT and clinical deterioration and did not show improved functional outcome for those receiving CVT. 43 However, this trial was limited by small sample size and large organizations still recommend consideration of EVTs for CVT in appropriate patient populations.…”
Section: Intracranial Venous Pathologies and Treatments Idiopathic In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies of EVTs for CVT have had mixed results, but generally show improved clinical outcomes with mechanical thrombectomy among those with severe deterioration despite systemic therapies, 41 although a recent large propensity-matched analysis from ACTION CVT showed no evidence of EVT benefit for CVT. 42 A randomized trial compared EVT to systemic anticoagulation in patients with acute CVT and clinical deterioration and did not show improved functional outcome for those receiving CVT. 43 However, this trial was limited by small sample size and large organizations still recommend consideration of EVTs for CVT in appropriate patient populations.…”
Section: Intracranial Venous Pathologies and Treatments Idiopathic In...mentioning
confidence: 99%
“…Observational studies of EVTs for CVT have had mixed results, but generally show improved clinical outcomes with mechanical thrombectomy among those with severe deterioration despite systemic therapies, 41 although a recent large propensity-matched analysis from ACTION CVT showed no evidence of EVT benefit for CVT. 42…”
Section: Intracranial Venous Pathologies and Treatmentsmentioning
confidence: 99%
“…54 Larger studies and meta-analyses showed that EVT is associated with higher mortality and no evidence of benefit with EVT. 55–58…”
Section: Therapeutic Advances In the Management Of Cvtmentioning
confidence: 99%
“…31 If there is suspicion of DAVF, the patency of the dural sinuses, as well as the cerebral venous drainage patterns, need to be carefully evaluated. [32][33][34] In carotid-cavernous fistulas (CCFs), CT and MRI may demonstrate dilatation of the cavernous sinuses and the superior ophthalmic veins (►Figs. 3 and 4).…”
Section: Radiological Diagnosismentioning
confidence: 99%